Prosthetic rehabilitation of oral submucous fibrosis patients: A systematic review of published case reports and case series. - Shankargouda Patil; Sachin Chakradhar Sarode; Gargi S Sarode; Shilpa Bhandi; Kamran Habib Awan; Marco Ferrari (PLoS ONE, 2017)
Background Oral submucous fibrosis (OSF) is an insidious chronic condition characterized by restricted mouth opening. Prosthetic rehabilitation is challenging for OSF patients as obtaining a good impression requires adequate mouth opening. The aim of the present review is to systematically present the data from case reports published in the English-language literature. Method A comprehensive search of the literature databases (PubMed, Medline, SCOPUS, Web of Science and Google Scholar) along with the references of published articles on prosthetic rehabilitation in OSF patients published to date was conducted. Keywords included a combination of 'Oral submucous fibrosis', 'prosthesis', 'dentures' and/or 'restricted mouth opening'. Citations from selected references and bibliographic linkages taken from similar cases were included in this review. The inclusion criteria selected for case reports on prosthetic rehabilitation in OSF patients, and cases of restricted mouth opening due to causes other than OSF were excluded from the study. Results A total of 21 cases were identified and analysed from 17 papers published in the English-language literature. Of these, 9 cases employed the sectional denture technique, 4 cases emphasized the need-based treatment approach in which conventional methods were modified, and 4 cases used mouth exercising devices. Finally, 1 case each involved, flexible denture, oral screen prosthesis, oral stents, surgery in conjunction with dentures. Conclusion Prosthetic rehabilitation in OSF patients is a multifaceted approach and should be patient specific, although sectional dentures have achieved the best results.